On Bregman Best Proximity Points in Banach Spaces. (3rd April 2017) - Naraghirad, Eskandar
ABSTRACT: In this article, using Bregman functions and Bregman distances, we first introduce the notion of Bregman best proximity points, extending the notion of best proximity points introduced and studied in [1 ]. We then prove existence and convergence results of Bregman best proximity points for Bregman cyclic contraction mappings in the setting of Banach spaces. It is well known that the Bregman distance does not satisfy either the symmetry property or the triangle inequality which are required for standard distances. Numerical examples are included at the end of the paper. So, our results improve and generalize many known results in the current literature.